PENGARUH STEROL LEMBAGA GANDUM (Triticum sp.) TERHADAP PROFIL LIPIDA DARAH TIKUS - Sri Anna Marliyati; Hidayat Syarief; Deddy Muchtadi; Latifah Darusman; Rimbawan Rimbawan; Bambang Pontjo Priosoerjanto (Media Gizi dan Keluarga, 2004)
ABSTRACT. The role of fitosterol in preventing cholesterol absorption and reducing atherosclerosis risk has been reported. This research was conducted to evaluate the effect of wheat germ sterol on the concentration of total cholesterol, LDL, HDL, triglycerides, and lesion formation in mice. In this research work. Sprague Dawley mice at the age of 2 months  (productive age) were used A random block design was employed with the following treatment on each experimental unit: Po (basal diet, negative contra/), PI (basal diet with cholesterol added, positive control), P2 (basal diet with cholesterol and ground wheat germ added), P3 (basal diet with cholesterol and wheat germ oil added). P4 (basal diet with cholesterol and wheat germ sterol added). 'and P5 (basal diet with cholesterol and wheat germ sterol supplemented margarine). Each mouse was d.esigned to intake 0.0343 g ofsterol daily, except those of negative control (Po) and positive control (PI). In order to increase cholesterol concentration in blood serum ofmice, 20 mglkg-body weight per day ofpropyltiourasil (PTU) was added into each diet. A set oftests was carried out to observe the concentrations of total cholesterol. LDL, HDL, and tryglycerides in blood serum of test animals, and mouse aorta micrographs. Results showed that wheat germ sterol could prevent the increase ofcholesterol in the blood ofmice. Feeding with sterol (P4) or sterol-supplemented margarine (P5) prevented the increase of total cholesterol after I month of experimentation, however, only P4 sustained the same condition after 2 months ofexperimentation. Feeding with wheat germ sterol (P4) was also the only treatment that prevented the increase of LDL cholesterol after 2 month of experimentation, and it was not different significantly with negative control (Po). Results of experimentation also showed that the concentration of HDL in serum blood of mice was not affected by wheat germ sterol. Unsurprisingly, there was no lesion ofatherosclerosis observed in all treatments used in this research. This result confirmed that mouse is resistant to atherosclerosis. Keywords: wheat germ sterol, mouse, total cholesterol, LDL, HDL, triglycerides. atherosclerotic lesions